Geopolitical risk and decoupling: Evidence from U.S. export controls - Matteo Crosignani; Lina Han; Marco Macchiavelli; André F. Silva (Federal Reserve Bank of New York, 2024)
Amid the current U.S.-China technological race, the U.S. has imposed export controls to deny China access to strategic technologies. We document that these measures prompted a broad-based decoupling of U.S. and Chinese supply chains. Once their Chinese customers are subject to export controls, U.S. suppliers are more likely to terminate relations with Chinese customers, including those not targeted by export controls. However, we find no evidence of reshoring or friend-shoring. As a result of these disruptions, affected suppliers have negative abnormal stock returns, wiping out 130 billion in market capitalization, and experience a drop in bank lending, profitability, and employment.
Keywords: G12; F51; F38; 330; geopolitical risk; export controls; decoupling; supply chains